GeoGebra, Quizizz, PowToon and Kahoot as technological resources in the teaching of Geometry in the seventh year of Costa Rican Basic General Education - Bolaños Víquez, Adriana (2020)
The present study aimed to analyze the influence of the use of technology in the processes of learning Mathematics; specifically, the content of geometry at the seventh grade by implementing a Didactic Unit in which GeoGebra, Quizizz, PowToon and Kahoot applications were used. This qualitative research included a group of teachers and two sections of seventh graders at the Liceo Experimental Bilingüe de Grecia Costa Rica. One of the sections was the control group and the other the experimental group. For the collection of the data, observations, questionnaires and field notes were used. The findings revealed that the applications implemented contributed to the motivation of the students in class. In addition, the implementation of the applications allowed the students to attain a better visualization of the geometric figures. Therefore, the study showed that the incorporation of these applications is beneficial to the teaching and learning of the content of Geometry in the seventh grade